DAMPAK INVESTASI ENERGI TERBARUKAN TERHADAP EMISI KARBON DI NEGARA OECD - Sukmawati, Mega Listiani; Hariyani, Happy Febrina (Journal of Financial Economics & Investment, 2025)
Global warming causes various negative impacts such as decreased productivity, rising sea levels, and losses in the agricultural sector which ultimately have a negative impact on GDP. Many economic sectors rely on fossil fuels, increasing carbon dioxide emissions, which worsen global warming. In OECD countries, although the economy continues to grow, there are efforts to reduce emissions through energy efficiency and changes in economic structure. Renewable energy has emerged as an important solution to reduce carbon emissions and environmental damage, with renewable energy consumption proving to be more effective in driving economic growth than fossil fuels. This study aims to examine the impact of renewable energy investment on carbon emissions in OECD countries, with the main variables including renewable energy, GDP, electricity generation, and CO₂ emissions. This study uses a panel regression method consisting of 18 OECD countries for the period 2013-2021 with a Random Effect Model. The results of the study show that Renewable Energy Investment, GDP and Power Generation have an effect on CO2 Emissions in OECD countries. The implication is to create policies on CO2 emission reduction targets in OECD countries while maintaining economic growth and energy security.